Relative effectiveness of alternative sequencing of middle-school science curriculum in terms of classroom learning environment and student attitudes - Long, Christopher Sean (Curtin University, 2013)
This study compared the relative effectiveness of two middle-school science curriculum sequences in terms of the learning environment and student attitudes towards science, as well as the differential effectiveness of the two curriculum sequences for minority and non-minority students. Additionally, associations between learning environment and student attitudes were examined. The sample consisted of 365 students in 15 grade 8 science classes in California and Texas.